Klasifikasi Penyakit Kulit Pada Manusia Menggunakan Metode Binary Decision Tree Support Vector Machine (BDTSVM) (Studi Kasus: Puskesmas Dinoyo Kota Malang) - Dyan Dyanmita Putri; Muhammad Tanzil Furqon; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The skin is an organ in the human body is very important because it lies on the outside of the body that serves to receive stimuli such as touch, pain and other influences from the outside. Skin disease is one of the most common diseases in tropical countries such as Indonesia. The lack of knowledge about the type of skin disease and do not know how to prevent it cause a person can get acute skin disease. So with the help of computer technology is expected to attack the skin of the human body can be detected early and it can minimize the occurrence of more dangerous diseases. This research aims to determine the classification of skin diseases in humans using the method of Binary Decision Tree Support Vector Machine (BDTSVM) Based on the test results obtained the best accuracy of 97.14% with SVM parameter test that is the value of Î» (lambda) = 0,5, C (complexity) = 1, constant Î³ (gamma) = 0,01, and itermax = 10.